(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The objective of this paper is to investigate the material removal rate of 5% egg shell powder reinforced epoxy compositecompared with plain epoxy resin composite. Materials and Methods: Experiment was carried out for two groups namely Group 1 (Plain epoxy resin composite) and Group 2 (5% egg shell powder reinforced epoxy composite). The sample size calculation was done using a G power calculator, g-power was calculated, and pre-test power is 95%. Mean value and standard deviation are 0.3 and 0.04 respectively. 16 samples per group were taken for study. Egg shell contains calcium carbonate crystals. Eggshell contains 1% magnesium carbonate, 1% calcium phosphate, 4% organic matter, and 94% calcium carbonate. Statistical analysis was performed with the SPSS statistical tool. G power is taken as 80%. Results: It was inferred from the results that the material removal rate of the plain epoxy resin composite was 0.170 mm3/min and 5% egg shell powder reinforced epoxy composite was 0.280 mm3/min. The significance value obtained from statistical value analysis p=0.041 (p<0.05) and hence significant variation observed between the groups. Conclusion: Within the limitations of this study, it was found that the material removal rate of novel 5% egg shell powder laminated with epoxy composite was better than the plain epoxy resin composite. The analysis shows that speed and feed rate are the most important factors for material removal rate and point angle is the second most important factor. Aim: The objective of this paper is to investigate the material removal rate of 5% egg shell powder reinforced epoxy composite compared with plain epoxy resin composite. Materials and Methods: Experiment was carried out for two groups namely Group 1 (Plain epoxy resin composite) and Group 2 (5% egg shell powder reinforced epoxy composite). The sample size calculation was done using a G power calculator, g-power was calculated, and pre-test power is 95%. Mean value and standard deviation are 0.3 and 0.04 respectively. 16 samples per group were taken for study. Egg shell contains calcium carbonate crystals. Eggshell contains 1% magnesium carbonate, 1% calcium phosphate, 4% organic matter, and 94% calcium carbonate. Statistical analysis was performed with the SPSS statistical tool. G power is taken as 80%. Results: It was inferred from the results that the material removal rate of the plain epoxy resin composite was 0.170 mm3/min and 5% egg shell powder reinforced epoxy composite was 0.280 mm3/min. The significance value obtained from statistical value analysis p=0.041 (p<0.05) and hence significant variation observed between the groups. Conclusion: Within the limitations of this study, it was found that the material removal rate of novel 5% egg shell powder laminated with epoxy composite was better than the plain epoxy resin composite. The analysis shows that speed and feed rate are the most important factors for material removal rateand point angle is the second most important factor.